2004
DOI: 10.1089/pho.2004.22.499
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy on Arthritis Induced by Urate Crystals

Abstract: Laser therapy has an anti-inflammatory effect in arthropathy induced in rats injected with urates, determined by fibrinogen levels and by histological involution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…A study by Xavier et al [26] showed that LED could inhibit the early chemotactic effects of inflammatory mediators by inhibiting COX. Similar results were observed by Campana et al [27], who reported that LED therapy acted in the early stages of inflammation since a decrease in COX-2 mRNA was observed. Previous studies have shown that low-intensity LED could significantly reduce the mRNA expression of COX [28, 29], precursors such as phospholipase A2 (PLA2), and reactive oxygen species (ROS) [28].…”
Section: Discussionsupporting
confidence: 90%
“…A study by Xavier et al [26] showed that LED could inhibit the early chemotactic effects of inflammatory mediators by inhibiting COX. Similar results were observed by Campana et al [27], who reported that LED therapy acted in the early stages of inflammation since a decrease in COX-2 mRNA was observed. Previous studies have shown that low-intensity LED could significantly reduce the mRNA expression of COX [28, 29], precursors such as phospholipase A2 (PLA2), and reactive oxygen species (ROS) [28].…”
Section: Discussionsupporting
confidence: 90%
“…The side effects caused by NSAIDs represent 25% of all secondary effects of these drugs, and NSAID use causes 25% of all gastro-duodenal ulcers. 32 In light of the conflicting results published to date, [17][18][19][20][21][22][23][24] it is clear that the use of LLLT to treat rheumatic pathologies requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…However, although there is much in the literature about the therapeutic effects of low-level laser therapy (LLLT), some of the literature shows contradictory results. [17][18][19][20][21][22][23][24] The process by which LLLT stimulates cellular function is called photostimulation. 25,26 We agree with other authors who study this therapy through experimental research, in an effort to clarify the interactions of light energy with cells and molecules, because these represent an important challenge to the clinician.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Moreover, laser radiation can improve microcirculation 15 and relieve pain both indirectly through the effects mentioned above, and directly, by acting on receptors and nerve endings. [16][17][18][19] Although many clinical studies give evidence for the effectiveness of IR laser therapy in the treatment of muscular disorders, thus justifying the wide application of laser treatments in clinical rehabilitation and sports medicine, in the literature there are conflicting results 1,[20][21][22][23][24][25][26][27] most likely caused by differences in the laser sources and treatment parameters that have been used. In the last few years significant progress has been made in understanding the mechanisms by which the IR laser therapy promotes the healing process and recovery of muscle tissue.…”
Section: Introductionmentioning
confidence: 99%